Abstract Filipe+Braumann+Roquete XVII ZOO - Filipe, Patrícia A. (2009)
Oral communication at the national conference XVII Congresso de Zootecnia (São Miguel, Açores, Portugal, Abril 2008). Web page: http://www.17zootecnia.com/ Study and parameter estimation of stochastic differential equation models for the growth of individual animals in randomly fluctuating environments.